Influence of Story telling Marketing, Brand Ambassador, and Tagline on Purchase Decision of Lip Product Wardah - Sri Harjanti; Nanda Wahyu Oktavia (AIBPM Publisher, 2024)
This research aims to analyze and determine the effect of storytelling marketing, brand ambassador, and taglines on purchasing decisions Wardah lip products for Undergraduate Management Study Program Students of UPN “Veteran” Yogyakarta. Questionaires were distributed using nonprobability purposive sampling techniques, and regression analysis adopted to test the predetermined hypotheses. The results of this research show are: (1) Storytelling marketing, brand ambassador, and taglines together have a significant effect on purchasing decisions for Wardah lip products, (2) Storytelling marketing partially has a positive and significant effect on purchasing decisions for Wardah lip products, (3) Brand ambassador partially have a positive and significant effect on purchasing decisions for Wardah lip products, (4) Tagline partially has a positive and significant effect on purchasing decisions for Wardah lip productsKeywords:Storytelling Marketing; Brand Ambassador; Tagline; Purchase Decision